Numerical simulation of grounding current interference and corrosion laws of high voltage direct current transmission system on oil and gas pipelines - Shuhua ZHAO; Shaofei LI; Shuli WANG; Yongchao RAO; Yunfei DUAN; Tianliang LI (You-qi chuyun, 2022)
With the development of long-distance power transmission system, the electrochemical corrosion of buried oil and gas pipelines caused by stray current is becoming more serious. In particular, the grounding current interference of High Voltage Direct Current (HVDC) transmission system will cause serious electrochemical corrosion at the defects of pipeline anti-corrosion coating, which threatens the operation safety of pipelines. In this case, the stray current density distribution along the buried pipelines close to the grounding electrode was simulated and analyzed with the COMSOL software. Meanwhile, study was performed for the influence laws of various interference parameters (including the angle between pipeline and cable of HVDC system, the grounding current, the soil conductivity, the distance between pipeline and grounding electrode, and the pipeline radius) on stray current density distribution and interference corrosion along the pipelines. The results indicate that the interference corrosion is enhanced greatly when the distance between the pipeline and any grounding electrode was less than 5 km, and it is the most serious when the angle between the pipeline and the cable is 0°. In addition, other parameters also have great influence on the interference corrosion of pipeline. Therefore, the study results could provide theoretical basis and reference for the interference protection, maintenance and inspection of pipelines.